THE IMPACT OF CLIMATE CHANGE ON VETCH PRODUCTIVITY IN POLISSYA REGION OF UKRAINE - Kolosovska, V. V. (Scientific Progress & Innovations, 2020)
Vetch is one of the promising, but insufficiently studied crops in biological and economic terms. Vetch is a high-yielding, protein-rich and versatile crop: green fodder, grain, grass meal, hay and silage. High fod-der qualities are ensured not only by the presence of proteins, but also by vitamins and mineral salts, for which vetch is also rich. Vetch gives grain yield of 25–35 hundredweight/ha and accumulates up to 50–80 kg/ha of nitrogen in the soil. Vetch is widely grown in all areas of Ukraine. The purpose of the re-search is to evaluate agro-climatic conditions of vetch cultivation, as well as to evaluate vetch photosynthet-ic productivity and yield of vetch under climate change. Calculations and data analysis of vetch development phases according to the average long-term data and RCP 4.5 possible climate change scenario were con-ducted. The analysis of agro-climatic conditions of vetch cultivation was carried out. During the flowering period, the average decade air temperature for the base period was 13.4 o С. According to the scenario, the average decade temperature was expected to be slightly lower than the baseline (by 0.2 %). The amount of precipitation during this period under RCP 4.5 scenario will increase by 17 % (115 mm). Moisture supply under climate change will decrease by 2 %. During the flowering-ripening period, the average air tempera-ture on average long-term values was 18.1 °C. In the period from 2015 to 2050, according to the climate change scenario, it will be 17.8 °С, which will be lower than the average long-term by 0.3 °С. The amount of precipitation according to the average long-term data is 112 mm. According to the climate change scenario, the amount of precipitation will decrease by 9 % and will be 101 mm. The peculiarities of the dates of vetch development phases were analyzed using average long-term data and RCP 4.5 climate change scenario. Al-so, the analysis of photosynthetic productivity of vetch and grain yield under the conditions of climate change was carried out. There will be an increase in all indicators of photosynthetic productivity. This will result in increasing vetch yield. In the base period, the yield of vetch grain was 19.0 hundredweight/ha; ac-cording to RCP 4.5 scenario, in both cases the yield is expected to increase to 21.5–23.8 hundredweight/ha. After the calculations, we can say that RCP 4.5 scenario in the studied area is expected to significantly change the agro-climatic conditions of growth, development and formation of vetch productivity. Favorable conditions for vetch cultivation are expected.